Pengelolaan Taman Wisata Alam 17 Pulau Riung oleh BKSDA, Kabupaten Ngada NTT - Waka, Aurelius Basa Ndala; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i01.p04, 2022)
Nature Tourism Park 17 Riung Islands is administratively located in the Riung sub-district, Ngada Regency, NTT. This area has two types of ecosystems, namely land and water, making the Nature Tourism Park 17 Riung Island be one of the tourist attractions worth a visit This research was conducted to find out the management system carried out by BKSDA in managing Nature Tourism Park 17 Riung Islands, the study used a qualitative data analysis. The method used in the form of observation, in-depth interviews and documentation studies. Overall, the management of Nature Tourism Park 17 Riung Island carried out by BKSDA has a system that has been programmed, but there are some things that have not been maximized and require new information, for example in the promotion section, cooperative relations with local governments, and the addition of tourism facilities, and there is no specific division of labor. Keyword: Management, Method, profile of tourism.